AN ANALYSIS OF MULTI-MODAL DISCOURSE ON “COCA-COLA ADVERTISEMENT” - Willem Saragih (BAHAS, 2019)
Abstract Investigation into language seems to be never ending – not only in form and meaning but also in function and use in communication. In use, for example,  recently, social semiotics as the development of semiotics has witnessed the move from the dominance of monomodality to multimodality. Newspapers and magazines, computers,  and mass media in general have articulated multimodal texts (combinations of video, audio, written text, etc.)  that aim to reinforce, render more complex, or produce different meanings. This means that the investigation is more than about language, but  attends to the full range of communicational forms people use which covers image, gesture, gaze, posture and so on- and the relationships between them. This article presents a multimodal analysis on  video advertisement entitled “https://www.google.com/?Funny, Commercial  Coca-Cola, Producer, Director, Victor Pukkalsky- YouTube + 2014” accessed on January 13, 2016. This case study  describes and interprets the video in order to  give the concepts of description and interpretation in the perspective of multimodal semiotics as recommended by  Anstey and Bull (2010). By applying the systems of multimodal recommended it was found that  five aspects namely 1. Linguistic, 2. Visual, 3. Audio, 4. Gestural and 6 Spatial aspects of the advertisement in multimodal semiotics perspective are covered. Key Words:  multimodal, discourse, analysis, advertisement, video, coca-cola